“Proteinjury”: a universal pathological mechanism mediated by cerebrospinal fluid in neurodegeneration and trauma - Lazarev, Vladimir F.; Alhasan, Bashar A.; Guzhova, Irina V.; Margulis, Boris A. (Frontiers in Cell and Developmental Biology, 2025)
Cerebrospinal fluid (CSF) is a vital body fluid that supports the normal physiological functions of the brain and spinal cord. However, pathological conditions associated with injuries and neurodegenerative diseases lead to the accumulation of peptides, proteins, and their oligomers or aggregated forms in the CSF. In such cases, the CSF serves as a carrier and distributor of these pathogenic structures, facilitating secondary damage through the cytotoxic effects of protein aggregates. To describe this phenomenon, we introduce the term “proteinjury.” To date, accumulating experimental evidence has identified key protein complexes that contribute to proteinjury, particularly in the context of neurodegenerative diseases, traumatic brain injuries, ischemic strokes and others commonly associated with cell death and the appearance of formerly cytoplasmic proteins in the extracellular milieu. This review explores the mechanisms underlying the formation of pathogenic protein complexes in CSF, the diagnostic potential of CSF protein biomarkers, and the prospects for rehabilitation therapies aimed at preventing secondary damage mediated by pathogenic protein structures in CSF. Based on the findings discussed in this review, we conclude that proteinjury represents a universal and critical mechanism in the progression of various neurodegenerative disorders, and a deeper understanding of this phenomenon may provide new insights for the development of targeted interventions to improve clinical outcomes.